2017
DOI: 10.1186/s13098-017-0238-9
|View full text |Cite
|
Sign up to set email alerts
|

Association of metabolic syndrome and electrocardiographic markers of subclinical cardiovascular disease

Abstract: BackgroundThe metabolic syndrome (MetS) and its components are well-established risk factors for cardiovascular diseases (CVD). It is inconclusive whether MetS and MetS score are associated with electrocardiographic markers of subclinical CVD, therefore we investigated this in a population without pre-existing CVD.MethodsWe performed a cross-sectional analysis in the Netherlands Epidemiology of Obesity study, a population-based cohort including 6671 participants aged 45–65. We excluded participants with pre-ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
11
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 42 publications
(36 reference statements)
4
11
0
Order By: Relevance
“…The current study confirms the results of the previous studies that concluded that MetS increases the risk for cardiac arrhythmias (Elffers et al, 2017;Faramawi, Sall, et al, 2008;Faramawi, Wildman, et al, 2008). However, herein we used a superior ECG parameter, that is, spatial QRS|T angle, to conventional ECG parameters that are associated with cardiac arrhythmias such as the T-wave deviation and QT interval (Elffers et al, 2017;Faramawi, Sall, et al, 2008;Faramawi, Wildman, et al, 2008). When we adjusted for other ECG parameters: PR interval, corrected QT interval, QRS interval, and QRS amplitude, MetS remained associated with abnormal QRS|T angle.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The current study confirms the results of the previous studies that concluded that MetS increases the risk for cardiac arrhythmias (Elffers et al, 2017;Faramawi, Sall, et al, 2008;Faramawi, Wildman, et al, 2008). However, herein we used a superior ECG parameter, that is, spatial QRS|T angle, to conventional ECG parameters that are associated with cardiac arrhythmias such as the T-wave deviation and QT interval (Elffers et al, 2017;Faramawi, Sall, et al, 2008;Faramawi, Wildman, et al, 2008). When we adjusted for other ECG parameters: PR interval, corrected QT interval, QRS interval, and QRS amplitude, MetS remained associated with abnormal QRS|T angle.…”
Section: Discussionsupporting
confidence: 92%
“…Those who met criteria for MetS are at a higher risk of cardiovascular morbidity and mortality (Mccullough, 2011;Mottillo et al, 2010). The presence of MetS has been associated with several ECG markers of cardiovascular disease (e.g., QRS complex duration, QT interval, T-wave axis) in a population-based cohort (Elffers et al, 2017). Using data obtained from NHANES III, Faramawi, Sall, and Kareem (2008) determined the presence of MetS was associated with ECG markers of cardiovascular disease: T-wave axis deviation and QT interval.…”
mentioning
confidence: 99%
“…21 Surprisingly PR interval in our study was not at a significant relationship with metabolic syndrome. A cross-sectional analysis in the Netherlands 23 reported the mean of P and QRS axis 44.2 and 23.0 respectively in non-obese subjects which were near our results. Also, the same as our results, they observed a negative significant relationship between P and QRS axis with metabolic syndrome.…”
Section: Discussionsupporting
confidence: 71%
“…It is worth noting that some of these studies produced different results, indicating that although a few relevant studies exist in the world, this relationship continues to remain unknown. 14,23 Besides, knowing the effects of MetS and its components on ECG can be helpful for CVD risk prediction, and used by health authorities and decision-makers to change its epidemic spread in Iran. 24…”
Section: Introductionmentioning
confidence: 99%
“…LA diameter is longer in higher BMI group and males 15 . QRS axis and P axis angle are greater in patients with lower BMI and metabolic syndrome 16,17 . Heart axis is greater in patients with lower BMI and younger age 18 .…”
Section: Discussionmentioning
confidence: 98%